2004
DOI: 10.2337/diacare.27.6.1259
|View full text |Cite
|
Sign up to set email alerts
|

Biological Variation in HbA1c Predicts Risk of Retinopathy and Nephropathy in Type 1 Diabetes

Abstract: OBJECTIVE -We hypothesized that biological variation in HbA 1c , distinct from variation attributable to mean blood glucose (MBG), would predict risk for microvascular complications in the Diabetes Control and Complications Trial (DCCT). RESEARCH DESIGN AND METHODS-A longitudinal multiple regression model was developed from MBG and HbA 1c measured in the 1,441 DCCT participants at quarterly visits. A hemoglobin glycation index (HGI ϭ observed HbA 1c -predicted HbA 1c ) was calculated for each visit to assess b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
204
2
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(221 citation statements)
references
References 26 publications
12
204
2
3
Order By: Relevance
“…Some previous authors have argued that a high GA/A1C ratio is associated with postprandial glucose excursion, early progression to insulin therapy in type 2 diabetes, or other events [35,36]. A high G-gap, corresponding to a low GA/ A1C ratio in the present study, has been reported to be a predictive indicator of diabetic complications, especially diabetic nephropathy [3][4][5]7]. These differences of high and low GA/A1C ratios in various clinical aspects may reflect the difference between pathological glycation of albumin and hemoglobin in the circulation and within the cell, respectively.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Some previous authors have argued that a high GA/A1C ratio is associated with postprandial glucose excursion, early progression to insulin therapy in type 2 diabetes, or other events [35,36]. A high G-gap, corresponding to a low GA/ A1C ratio in the present study, has been reported to be a predictive indicator of diabetic complications, especially diabetic nephropathy [3][4][5]7]. These differences of high and low GA/A1C ratios in various clinical aspects may reflect the difference between pathological glycation of albumin and hemoglobin in the circulation and within the cell, respectively.…”
Section: Discussionsupporting
confidence: 54%
“…Deviations between mean blood glucose and A1C values with continuous glucose monitoring (CGM) have been shown to be consistent in each individual [39][40][41]. These deviations in mean blood glucose and the A1C value are called the glycohemoglobin index (GHI), and the biological variation of A1C has been examined [3,4,42,43]. The G-gap is also reported to be an indicator with biological variation [5,31], and Nayak et al [6] reported that the G-gap has consistent biological variability in individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated HbA1c level has also been linked to a higher risk of diabetic retinopathy [48], nephropathy [49], cardiovascular diseases [50,51] and premature death [52,53]. Other studies must be done to establish the best cut point of A1C that correlates with specific diabetic microvascular complications, especially when the diagnostic tests are discordant.…”
Section: Resultsmentioning
confidence: 99%
“…Essentially, the authors stressed that the agreement between the measurement of mean plasma glucose and A 1c in the DCCT was only approximately 50% according to a subsequent analysis [2], although the original data reported an agreement of 67% [3]. They presented well-known evidence that different treatment modalities for diabetes may have an impact on the agreement between mean plasma glucose and A 1c .…”
Section: A 1c Glycated Haemoglobin Adag a 1c -Derived Average Glucosementioning
confidence: 98%